ROR2, a driver of “phenotype switching” in melanoma? - Lopez Bergami, Pablo Roberto (2022)
Receptor tyrosine kinase-like orphan receptor 2 (ROR2) is a receptor for the Wnt5a ligand that was shown to play a dual role in cancer. ROR2 was shown to either suppress or promote tumor progression in different tumor types by regulating the same biological processes (i.e. proliferation, invasion) in opposite ways. We have recently observed that ROR2 plays multiple and somewhat contradictory roles in melanoma where it impairs cell proliferation but promotes migration, EMT and chemoresistance. In the present article, ROR2 is proposed to be a major driver of “phenotype switching” in melanoma that can tilt the cellular behavior toward proliferative or invasive phenotypes. This function of ROR2 has therapeutic implications since it would provide an opportunity for targeting specific phenotypes such as invasive and drug-resistant ones by inhibiting ROR2.